Theoretical and practical reviews of the Indonesian translated “Harry Potter and the Sorcerer’s Stone” novel - Zulfadli A. Aziz (Universitas Syiah Kuala, 2015)
This paper investigates the results of translation of the English novel “Harry Potter and the Sorcerer’s Stone” into Indonesian. The Indonesian version of the novel was compared with the English original one to find the translation practices used by the translator. The translation was analysed by focusing on the strategies the translator used in translating the text from the Second Language into the Target Language. It was found that the translator of the novel used four strategies: foreignization and domestication, cultural equivalences, zero-translation, and pragmatic translation. Furthermore, the cultural differences and new words which were created by the original author were the most difficult ones to find equivalences for in Indonesian. The translator tended to use original words from the source text un-translated into the TL. As a result, the target text does not read smoothly, or naturally, and may sound “foreign” to readers. It is suggested that translators should attempt to translate literary works by applying proper translation theory and practice.